Maternal and neonatal variables affecting CD34+ cell count in the umbilical cord blood - Satya Prakash; Ashish Jain; Deepak Pahwa; Jaswinder Kaur Kalra; Rattiram Sharma (Journal of Applied Hematology, 2022)
INTRODUCTION: Ease of collection, ready availability and lower graft-versus-host disease compared to peripheral blood stem cell favored umbilical cord blood stem cell transplantation. AIM: To assess the maternal and neonatal predictor affecting total nucleated and CD34+ cell count in cord blood collections. METHOD: A total of 200 Cord blood units were collected under aseptic conditions. Volume reduction was made by 6% hydroxyethyl starch followed by upright centrifugation of cord blood units to obtain a cellular pellet. Differential cell counts were done through hematology analyzer, viability testing by trypan blue exclusion test and percentage CD34, and CD45 estimation by flow cytometry. Two samples were HBsAg positive and not included in the study. RESULT: Total CD34 positive cell counts were more in cord blood units collected from younger age mother. Higher birth weight of newborns yielded a larger volume of cord blood unit and higher absolute TNC and CD34+ cell counts. The placental weight was positively correlated with the volume of cord blood collected, birth weight of new born, and total nucleated cell count but no correlation was observed with absolute CD34+ cell counts. The gravida status, gestational age and method of delivery were not significant with total nucleated cell (TNC), mononuclear cell (MNC), and CD34+ counts. CONCLUSION: Maternal age, birth weight, placental weight, and volume of CBUs were the most important predictor of getting increased nucleated and CD34+ cells in cord blood. Moreover, CBUs collected from pre-term deliveries were shown to have an approximately equal absolute number of CD34+ cells.